Analisis Pemasaran Usaha Mikro Kecil Menengah Kerajinan Bambu Sebelum Dan Selama Covid-19 Di Warung Kenzo Kelurahan Kinilow Kecamatan Tomohon Utara Kota Tomohon - Tatuh, Jusiana Veronika; Timban, Jean Fanny Junita; Talumingan, Celcius (Sam Ratulangi University, 2023)
This study aims to determine the benefits before and during the Covid-19 pandemic for Bamboo Crafts MSMEs at Warung Kenzo in the Kinilow Village, North Tomohon District, Tomohon City. This research was conducted from March to May 2022. The location of the research was carried out in the Kinilow Village, Tomohon Utara District, Tomohon City. The data in this study consisted of primary data and secondary data. The sampling method in this study was purposive sampling. The variables studied were the characteristics of the respondents, business characteristics, and the impact of the Covid-19 pandemic on income. The analytical method used in this study is a qualitative descriptive analysis method. The results of the study showed that the average profit of bamboo handicraft owners at Warung Kenzo before the co-19 pandemic was Rp.981,167/month and profits during the co-19 pandemic were Rp.10,442,500/month. This proves that Covid-19 has had a positive impact on micro, small and medium enterprises for bamboo handicrafts at Warung Kenzo in the Kinilow Village.